Aplikasi Kompos Tandan Kosong Kelapa Sawit dan Mikoriza Arbuskula Untuk Meningkatkan Pertumbuhan Bibit Manggis (Garcinia mangostana L.) - serlina, Mauli; sjofjan, Jurnawaty; yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Abstrac Mangosteen (Garcinia mangostana L.) is one of the most Indonesian favored fruit, because the ripe fruit (ripe) has a distinctive taste, sweet, sour and fresh. The main problem encountered in the cultivation of mangosteen is to provide theseeds. Weak mangosteen plant roots decrease growth level. This study aims to determine the interaction of palm oil empty bunches compost with Arbuscular Mycorrhiza on the seed growth of mangosteen and get the best dose. This research was conductet AgricultureFaculty, University of Riau campus Bina Widya Tampan, Pekanbaru lastedOctober 2012 until January 2013. The results of shows that by using TKKS compost with a dose of 150 g/polybag and the use of mycorrhizae 15g/polybag is better than giving 150 g/polybag and mhycorrizhal 20 g/polybag because the results are not significantly different. To get the combination use of empty fruit bunches of oil palm compost and mycorrhizal needs to be done in a long time , to get more tangible results. Keywords :Mangosteen, interaction, arbuscular mycorrhizal